Metabolic Injury of Hepatocytes Promotes Progression of NAFLD and AALD - Carvalho-Gontijo, Raquel; Han, Cuijuan; Zhang, Lei; Zhang, Vivian; Hosseini, Mojgan; Mekeel, Kristin; Schnabl, Bernd; Loomba, Rohit; Karin, Michael; Brenner, David A.; Kisseleva, Tatiana (Seminars in Liver Disease, 2022)
Nonalcoholic liver disease is a component of metabolic syndrome associated with obesity, insulin resistance, and hyperlipidemia. Excessive alcohol consumption may accelerate the progression of steatosis, steatohepatitis, and fibrosis. While simple steatosis is considered a benign condition, nonalcoholic steatohepatitis with inflammation and fibrosis may progress to cirrhosis, liver failure, and hepatocellular cancer. Studies in rodent experimental models and primary cell cultures have demonstrated several common cellular and molecular mechanisms in the pathogenesis and regression of liver fibrosis. Chronic injury and death of hepatocytes cause the recruitment of myeloid cells, secretion of inflammatory and fibrogenic cytokines, and activation of myofibroblasts, resulting in liver fibrosis. In this review, we discuss the role of metabolically injured hepatocytes in the pathogenesis of nonalcoholic steatohepatitis and alcohol-associated liver disease. Specifically, the role of chemokine production and de novo lipogenesis in the development of steatotic hepatocytes and the pathways of steatosis regulation are discussed.
Keywords: liver fibrosis; steatotic hepatocytes; de novo lipogenesis; endoplasmic reticulum stress; unfolded protein response